Current controversies with oral emergency contraception. (17th July 2017) - Cameron, ST; Li, HWR; Gemzell‐Danielsson, K
Abstract : Emergency contraception (EC) is a method to be used in the case of unprotected sexual intercourse, failure of a regular contraceptive method, or after rape to try to prevent an unintended pregnancy. Oral EC remains surrounded by controversy, much due to myths and misconceptions among the public, policy makers and healthcare providers. This has resulted in restrictions on its availability in many parts of the world and restrictions on women's access to it. The aim of this article is to provide an evidence‐based view on some of these common controversial issues surrounding oral EC in clinical practice. Tweetable abstract: Controversy about emergency contraception restricts access for women. Tweetable abstract: Controversy about emergency contraception restricts access for women.